Textos narrativos: oportunidad para fortalecer la lectura crítica en las estudiantes de 5° de básica primaria del colegio Marie Poussepin (2016)
This research project aims to determiner the effects of the application of analysis of narrative texts in the students of 5th primary basic of Marie Poussepin College to strengthen critical reading. By applying a quasi-experimental design and taking as theoretical column approaches around reading Cassany (1997), the principles of critical reading (Campos Arenas, 2007), critical thinking (Santiuste Bermejo, V. (Coord.), Ayala, C., Barrigüete, C., García, E., González, J., Rossignoli, J., & Toledo, E. 2001), reading levels (MEN Guidelines, 1998). From the shortcomings observed in the framework of the applied testing (pretest in the Experimental groups 5th D and Control 5 ° C), it was considered appropriate to undertake the design of the proposed intervention based on six workshops (only the experimental group) namely type based on the use of narrative texts, images and graphics. Through the implementation and evaluation of the proposal and the results of the posttest, they were able to determine the results relative to the initial state intervened students compared to the nonintervention group.